La poesia catalana i el boom de l'any 1972 - Aulet, Jaume (Caplletra. Revista Internacional de Filologia, 1997)
The year of 1972 is a very important date in the understanding of the evolution of Catalan poetry, during the decade of the 70's. The changes in this year make up the basic framework for the future characterization of the genre. The article aims to establish a syncronized break away from the year previously mentioned to choose the objective facts that this break demonstrates and interpret them in order to show the repercussion of all. There are four basic elements: the death of Gabriel Ferrater; the publication of three fundamental poetry books by significant poets (Pere Gimferrer, Narcís Comadira and Francesc Parcerisas); the appearance of new names like Xavier Bru de Sala or Ramon Pinyol, and the formatiom of the magazine group Tarotdequinze.